A Phase IB/IIA Study of Allogeneic, Bone Marrow-derived, Mesenchymal Stem Cells for the Treatment of Refractory Ileal-anal Anastomosis and Peripouch Fistulas in the Setting of Crohn's Disease of the Pouch. (2nd November 2022) - Lightner, Amy L; Reese, Jane; Ream, Justin; Nachand, Douglas; Jia, Xue; Pineiro, Ana Otero; Dadgar, Neda; Steele, Scott; Hull, Tracy
Abstract: Background and Aims: Mesenchymal stem cells [MSCs] have been used for the treatment of perianal Crohn's fistulising disease by direction injection. No studies to date have included patients with an ileal pouch-anal anastomosis [IPAA] in situ . Methods: A phase IB/IIA, randomised, control trial of bone marrow-derived, allogeneic MSCs via direct injection to treat adult patients with a peripouch fistula[s] was conducted; 75 million MSCs were administered with a 22 G needle, with repeat injection at 3 months if complete clinical and radiographic healing was not achieved. Adverse and serious adverse events at post-procedure Day 1, Week 2, Week 6, Month 3, Month 6, and Month 12 were assessed. Clinical healing, radiographic healing per pelvic magnetic resonance imaging [MRI], and patient-reported outcomes were assessed at the same time points. Results: A total of 22 patients were enrolled and treated; 16 were treated and six were controls. There were no adverse or serious adverse events related to MSC therapy. At 6 months, 31% of the treatment group and 20% of the control had complete clinical and radiographic healing. When stratifying the treatment group into perianal [ n = 7] and ano-vaginal [ n = 8] fistulas, 6-month healing in the treatment groups was 57% and 0%, respectively. The perianal Crohn's disease activity index [PCDAI], Wexner incontinence score, and van Assche score all significantly decreased in treatment patients at 6 months; only the PCDAI decreased in the control group. Conclusion: Bone marrow-derived, allogeneic MSCs offer a safe and effective alternative treatment approach for peripouch fistulas in the setting of a Crohn's like phenotype of the pouch [ClinicalTrials.gov Identifier: NCT04519684.]